DISKURSUS PENDIDIKAN ISLAM BERWAWASAN LINGKUNGAN DENGAN PENDEKATAN TAFSIR MAUDHU’I - Akhmad Alim; Bahrum Subagiya (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The issue of environmental damage has become a concern of the international community. World leaders come together to find solutions to address the impacts of environmental degradation in different parts of the world. One of the important points to raise public awareness is through education, by teaching environmental education. The purpose of this study is to offer an environmentally friendly Islamic education approach with the Tafsir Maudhu'i approach, in which Islamic education has a role in public awareness to protect the environment and preserve nature. The method used in this research is thematic interpretation or Maudhu'i interpretation. The results of this study reveal that the Qur'an and Hadith have hinted at humans to protect and preserve the environment. Although in the Qur'an the word environment is not explicitly mentioned, the components that make up the environment and their interactions have been explained clearly. The purpose of Islamic education with an environmental perspective with a maudhu'i interpretation approach is to form humans who believe in Allah and the Last Day. The methods that can be used are tadabur, contemplation, and direct practice in the field in preserving the environment as exemplified by the Prophet.